High-resolution imaging of autofluorescent particles within drusen using structured illumination microscopy - Roßberger, Sabrina; Ach, Thomas; Best, Gerrit; Cremer, Christoph; Heintzmann, Rainer; Dithmar, Stefan (British journal of ophthalmology, 2013)
Purpose Autofluorescent (AF) material within drusen has rarely been described and there is little knowledge about origin and formation of these particles. Drusen formation is still a relatively unknown process and analysis of AF inclusions might be important for the understanding of fundamental processes. Here we present a detailed analysis of drusen containing AF material using structured illumination microscopy (SIM), which provides a lateral resolution twice as high as conventional fluorescence microscopy. - Methods Eight histological retinal pigment epithelium (RPE) sections obtained from eight human donor eyes (76±4 years) were examined by SIM using laser light of different wavelengths (488 nm, 568 nm). Drusen were studied with regards to their size and shape. AF material within drusen was analysed in terms of size, shape, AF behaviour, and distribution across drusen. - Results A total of 441 drusen were found, of which 101 contained AF material (22.9%). 90.1% of these drusen were smaller than 63 µm (mean: 35.65 µm±2.38 µm) regardless of whether classified as hard or soft drusen. AF particles (n=190) within drusen show similar spectra compared with lipofuscin granules in RPE cells. Up to 11 particles were found within a single druse. Nearly all particles were located in the outer 2/3 of the drusen (85.94%). - Conclusions SIM allows studying AF particles within drusen on a higher resolution level compared with conventional fluorescence, multiphoton or even confocal microscopy and therefore provides detailed insights in drusen. Shape and autofluorescence analysis of the material embedded in drusen suggest that these particles originate from the overlaying RPE cells.
Gesehen am 20.01.2022